Beautiful people : my thirteen truths about disability - Blake, Melissa (Blogger) (Hachette Go, an imprint of Hachette Book Group, Inc., 2024)
Well-known disability activist and social media influencer Melissa Blake offers a frank, illuminating memoir and a call to action for disabled people and allies. In the summer of 2019, journalist Melissa Blake penned an op-ed for CNN Opinion. A conservative pundit caught wind of it, mentioning Blake's work in a YouTube video. What happened next is equal parts a searing view into society, how we collectively view and treat disabled people, and the making of an advocate. After a troll said that Blake should be banned from posting pictures of herself, she took to Twitter and defiantly posted three smiling selfies, all taken during a lovely vacation in the Big Apple. -- Provided by publisher.